Front Cover: Lithium–Bromide Exchange versus Nucleophilic Addition of Schiff's base: Unprecedented Tandem Cyclisation Pathways (Chem. Eur. J. 51/2019). Issue 51 (13th August 2019) - Orr, Samantha A.; Border, Emily C.; Andrews, Philip C.; Blair, Victoria L.
Abstract : Book‐breaking lithium–bromide exchange : Metal–halogen exchange is one of the most powerful and widely used synthetic tools for the functionalisation of aromatic molecules with the topic appearing in many textbooks in the chemistry section of the library (pictured: Melbourne State Library). This work writes a new chapter for these textbooks whereby traditional lithium–bromide exchange literature outcomes have been challenged by imines. Instead, competitive nucleophilic addition and cascade cyclisation pathways lead to a plethora of products; amines, iso ‐indolinones and anthracenes (highlighted in the book in the cover artwork). Various factors are studied including solvent choice, sterics, organolithium reagent and stoichiometry. More information can be found in the Full Paper by P. C. Andrews, V. L. Blair, et al. onpage 11876 .